Tokens improve capuchin performance in the reverse–reward contingency task - Addessi, Elsa (The Royal Society, 2011)
In humans and apes, one of the most adaptive functions of symbols is to inhibit strong behavioural predispositions. However, to our knowledge, no study has yet investigated whether using symbols provides some advantage to non-ape primates. We aimed to trace the evolutionary roots of symbolic competence by examining whether tokens improve performance in the reverse–reward contingency task in capuchin monkeys, which diverged from the human lineage approximately 35 Ma. Eight capuchins chose between: (i) two food quantities, (ii) two quantities of ‘low-symbolic distance tokens’ (each corresponding to one unit of food), and (iii) two ‘high-symbolic distance tokens’ (each corresponding to a different amount of food). In all conditions, subjects had to select the smaller quantity to obtain the larger reward. No procedural modifications were employed. Tokens did improve performance: five subjects succeeded with high-symbolic distance tokens, though only one succeeded with food, and none succeeded with low-symbolic distance tokens. Moreover, two of the five subjects transferred the rule to novel token combinations. Learning effects or preference reversals could not account for the successful performance with high-symbolic distance tokens. This is, to our knowledge, the first demonstration that tokens do allow monkeys to inhibit strong behavioural predispositions, as occurs in chimpanzees and children.